Awareness, Attitude, Implementation and Academic Performance in Science Curriculum: A Correlational Study - Balinario, Jick C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The descriptive-correlational research examined the awareness, attitude, and implementation of science spiral curriculum concerning students’ academic performance. Findings revealed that teachers are moderately aware, have a favorable attitude, and moderately implemented the science curriculum, including objectives, methodology, learning resources, and assessment were relatively implemented while facilities were less implemented. It was also determined that they have a satisfactory rating in a science subject regarding students’ performance. The level of awareness, attitude, and implementation of the K to 12 science curriculum regarding sex, academic qualification, and teaching length had no significant difference. Finally, it revealed further that the level of awareness, attitude, and implementation of the spiral progression curriculum to students’ academic performance has no significant relationship to the aforementioned variable. Thus, enhancement programs, skills training, and the procurement of science laboratory equipment are needed to enhance the educational process to meet the K to 12 science curriculum set standards